Stratigraphic Modelling of the Lower/Middle Oxfordian (Upper Jurassic) Outer Ramp Deposits from the NE Paris Basin (France) - Morales, Chloé; Pellenard, Pierre; Vincent, Benoit; Smektala, Franck; Daniau, Fleur; Landrein, Philippe (Geosciences, 2022)
We investigate herein the lateral and vertical lithological heterogeneities of the Lower/Middle Oxfordian deposits (“Terrain à Chailles” and “Marnes des Eparges” formations) in the north-eastern Paris Basin. This new detailed stratigraphic framework documents the evolution at high resolution of an outer ramp based on regional correlations in order to constrain the evolution of petrological properties between the clayey “Argiles de la Woëvre” Formation and the more calcareous “Marnes et Calcaires à Coraux de Foug Formation. The “Argiles de la Woëvre” Formation is targeted for the deep storage of nuclear waste in north-eastern France. Nine wells are correlated over the “Zone of Interest for Further Research” (ZIRA), defined by the French agency for radioactive waste management (Andra), with a resolution of 0.5–1.0 m. The architecture and the age control of these formations have been refined, revealing that the “Terrain à Chailles” Formation is characterised by a regular slightly inclined sedimentation gently deeping in the SW direction and shows a lithological evolution from silty claystones to an increased occurrence of its calcareous content towards the top (Lower Oxfordian, uppermost mariae and cordatum ammonite zones). The above “Marnes des Eparges” Formation, characterised by claystone limestone alternations, is assigned to the Middle Oxfordian (plicatilis ammonite zone), deposited during a slightly enhanced subsidence phase in the SE part of the basin and documented and associated with onlaps geometries on the more proximal areas. However, this change in geometry does not affect petrological properties over ZIRA, as this is not accompanied by lithological changes. The environmental factors controlling petrological heterogeneities over ZIRA are also discussed. The stepwise increase in the carbonate content and the decrease in the detrital content towards the Lower to Middle Oxfordian deposits was likely triggered by a climate change towards drier conditions, modulated by sea level changes on a ramp morphology. A major condensation phase encompassing most of the Lower Oxfordian cordatum ammonite zone is also highlighted. The occurrence of a maximum regressive surface associated with gentle slope topography is a probable trigger for condensation. Changes in geometries are, however, associated with the activity of the Metz Fault, which potentially had an influence on the subsidence rates of the basin at that time.